1991
DOI: 10.1161/01.hyp.18.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoadrenal control by paraventricular hypothalamic beta-endorphin in hypertension.

Abstract: The paraventricular hypothalamus regulates autonomic nerve outflow and is innervated with /3-endorphin-immunoreactlve nerve terminals. This study examined the effects of /3-endorphin microinjected into the paraventricular hypothalamus on blood pressure, heart rate, and plasma catecholamine and glucose concentrations in conscious, unrestrained spontaneously hypertensive rats (SHR) and Wistar-Kyoto (WKY) rats at the age of about 9 weeks. Thirty minutes after paraventricular hypothalamic injection of [ I n additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Thus, the present results were clearly es *P <0.05 for not due to leakage of DAMGO from its central site of injection up, analysis of into the periphery. Moreover, injection of aCSF (0.2 jul) into the PVN had no cardiovascular effects, indicating that dis- Pfeiffer et al, 1983b;Appel et al, 1986;Kiritsy-Roy et al, 1986;Siren et al, 1989), an increase in sympathetic outflow in peripheral postganglionic sympathetic nerves (Siren & Feuerstein, 1991), and blockade of the cardiovascular responses by adrenergic neuronal blocking drugs (Jin & Rockhold, 1991;Siren & Feuerstein, 1991;Pfeiffer et al, 1983b). Plasma adrenaline was far more sensitive to the effects of DAMGO in the PVN, suggesting that the treatment produced a relatively selective activation of the adrenal medulla .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the present results were clearly es *P <0.05 for not due to leakage of DAMGO from its central site of injection up, analysis of into the periphery. Moreover, injection of aCSF (0.2 jul) into the PVN had no cardiovascular effects, indicating that dis- Pfeiffer et al, 1983b;Appel et al, 1986;Kiritsy-Roy et al, 1986;Siren et al, 1989), an increase in sympathetic outflow in peripheral postganglionic sympathetic nerves (Siren & Feuerstein, 1991), and blockade of the cardiovascular responses by adrenergic neuronal blocking drugs (Jin & Rockhold, 1991;Siren & Feuerstein, 1991;Pfeiffer et al, 1983b). Plasma adrenaline was far more sensitive to the effects of DAMGO in the PVN, suggesting that the treatment produced a relatively selective activation of the adrenal medulla .…”
Section: Discussionmentioning
confidence: 99%
“…Mainly, opioid peptides and opiate receptors have been found in specific brain nuclei, with an established role in the regulation of cardiovascular activities (Atweh & Kuhar, 1977;Hokfelt et al, 1977;Fallon & Leslie, 1986;Mansour et al, 1988;Desjardins et al, 1990), and potent cardiovascular effects have been reported following central administration of opioid peptides (Hassen et al, 1983;Pfeiffer et al, 1983a,b;Appel et al, 1986;Kiritsy-Roy et al, 1986;Marson et al, 1989a,b;May et al, 1989;Siren et al, 1989;Jin & Rockhold, 1991;Siren & Feuerstein, 1991). However, pharmacological studies with opioid ligands have revealed a complex pattern of cardiovascular responses, which has been attributed to the multiple opioid receptors, the type of opioid ligand and its selectivity toward specific opioid receptor, the state of consciousness of the experimental animals, the site(s) of injection and dosage, species, and experimental conditions (i.e., stressed versus resting animals) (Holaday, 1983;Feuerstein, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that central endogenous opioid peptides and receptors are involved in the regulation of salt ingestion. β‐endorphin, comprising one of these, plays a key role in the modulation of salt hedonic palatability and sodium appetite, as well as in dietary‐sodium‐overload induced sympathetic and pressor responses . Previous results from our laboratory indicated that β‐endorphin knockout mice and heterozygous mutant mice consume approximately 50% less 2% NaCl solution than wild‐type mice after sodium depletion, suggesting that β‐endorphin facilitates induced sodium appetite .…”
Section: Introductionmentioning
confidence: 91%